Of light and struggle : social justice, human rights, and accountability in Uruguay - Sharnak, Debbie (Power, politics, and the world., 2023)
"This book explores how activists, transnational social movements, and international policymakers responded, clashed, and collaborated during Uruguay's dictatorship and transition back to democratic rule. It uncovers the messy process through which human rights became a powerful discourse for social change, suggesting that discussions occurring around the globe about the small country on the Río de la Plata had international implications about the limits and possibilities of human rights well beyond Uruguay's shores"--